Deacetylation of HSC70-4 Promotes Bombyx mori Nucleopolyhedrovirus Proliferation via Proteasome-Mediated Nuclear Import - Mao, Fuxiang; Chen, Xi; Ngowo, Jonas; Zhu, Yajie; Lei, Jihai; Gao, Xu; Miao, Meng; Quan, Yanping; Yu, Wei (Frontiers in Physiology, 2021)
Silkworm (Bombyx mori) is a model organism with great agricultural economic value and plays a crucial role in biological studies. B. mori nucleopolyhedrovirus (BmNPV) is a major viral pathogen of silkworm leading to huge silk loss annually. In a recent lysine acetylome of silkworm infected with BmNPV, we focused on the heat shock cognate protein 70-4 (HSC70-4) lysine acetylation change due to the consequent nuclear accumulation and viral structure assembly. In this study, the viral genome replication, proliferation, and production of budded viruses (BVs) were restrained by the HSP/HSC70 inhibitor treatment. However, HSC70-4 overexpression enhanced BmNPV reproduction. Furthermore, site-direct mutagenesis for acetylated mimic (K/Q) or deacetylated mimic (K/R) mutants of HSC70-4 demonstrated that lysine 77 (K77) deacetylation promotes HSC70-4 stability, viral DNA duplication, and HSC70-4 nuclear entry upon BmNPV challenge, and the nuclear propulsion of HSC70-4 after viral stimulus might be dependent on the interaction with the carboxyl terminus of HSC70-interacting protein (CHIP, an E3 ubiquitin ligase), followed by ubiquitin-proteasome system assistance. In this study, single lysine 77 deacetylation of HSC70-4 was deemed as a part of the locomotive pathway for facilitating BmNPV proliferation and provided novel insights into the antiviral strategic development.